Change and Continuity on the Supreme Court - Linda Greenhouse (Washington University Journal of Law & Policy, 2007)
When two new Justices joined the Supreme Court during the 2005 term, the longest period of membership stability in the Court's modern history came to an end. The eleven years without personnel change, from 1994 until 2005, made this the longest “natural court,” as scholars call the period during which the same Justices serve together, since the 1820s. And not since the 1971 Term, a generation ago, when Justices Lewis Powell and William Rehnquist took their seats, have two new Justices joined the Court during a single term. Reprinted by permission of the publisher.
Keywords: Judicial process; Supreme Court justices (United States) – History; Judicial statistics; United States. Supreme Court; Youngstown Sheet & amp; Tube Co. v. Sawyer; Ex parte Quirin; Miranda v. Arizona; Executive power; Judicial power; Judicial selection; United States